Penggabungan Teori Konflik Strukturalist- Non - Marxist dan Teori Fungsionalisme Struktural - Talcott Parsons: (Upaya Menemukan Model Teori Sosial-Politik Alternatif sebagai Resolusi Konflik Politik dan Tindak Kekerasan di Indonesia) - Ismail Ismail (UIN Sunan Kalijaga Yogyakarta, 2012)
The convergence of the two theories between non-Marxist structuralist conflict theory and Talcott Parsons’ functionalism structuralist one contributes to an alternative model of social political theory used as conflict resolution and crime in Indonesia.The mentioned theories could not be optimally applied in terms of political government system in Indonesia.Without the convergence of the two political theories, it is urgent to seek for a particular political theory accommodated the pluralistic society in Indonesian condition. In this scene, the government should construct reconciliation strategy. Reconciliation is present if only the government appreciatively opens a discussion type of initiative in decision making. It leads to accommodate the peaceful type of approach to conflicts.It is urgent, in this regard, to solve the issues of economy, education, welfare, integration, and tribes conflicts. If the government has a good will, it bore to strong possibility in that conflicts and violence could be clearly anticipated in an immediate resolution.